Actualization of Madrasah Organizational Culture and Environment Management at MI Al Khoiriyah Pakis District Malang Regency - Indah Hasnawati; Kewan Waled (P3M IAI Nusantara Batang Hari, 2022)
This study aims to obtain an empirical description of the strategic role of Human Resources as implementers of procedures and policies in education, alternative solutions in dealing with and minimizing obstacles in the madrasah environment. This research approach is a qualitative approach with descriptive methods with instruments in the form of observations, interviews, and reviewing documents at MI Al Khoiriyah Malang Regency. The results of the study illustrate that the strategic role of the madrasah head in developing an organizational culture to become a strong, conducive and responsible madrasa will benefit all madrasa residents, minimizing obstacles through actualization of the implementation of a positive madrasa organizational culture, supported by all madrasah personnel and it takes time to become a tradition/habituation, as well as from elements of the foundation, the madrasah committee contributes to efforts to provide advice and control over madrasah programs on an ongoing basis.